2010
DOI: 10.1891/0889-8391.24.2.132
|View full text |Cite
|
Sign up to set email alerts
|

CBT Basics: A Group Approach to Teaching Fundamental Cognitive-Behavioral Skills

Abstract: CBT Basics I is a psychoeducational group program originally developed as a pre-individual therapy introduction to cognitive-behavioral therapy (CBT) skills for clients presenting with depression and/or anxiety disorders. We describe the development and content of this sixsession introductory CBT group and provide data from a 3-year pilot program. The results support the potential for symptom improvement and CBT skill acquisition, and provide preliminary evidence for the group's potential to enhance accessibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Psychoeducation, an integral part of CBT, presents clients with mental health information in an attempt to teach them about the psychological processes underlying their distress and inform them of resources available to manage it [ 196 ]. A meta-analysis of 25 RCTs reported that the “Coping with Depression” psychoeducational intervention, developed by Lewinsohn et al [ 197 ], was effective at treating depression, albeit with a small effect size ( d =0.28, 95% CI 0.18-0.38) [ 102 ].…”
Section: Resultsmentioning
confidence: 99%
“…Psychoeducation, an integral part of CBT, presents clients with mental health information in an attempt to teach them about the psychological processes underlying their distress and inform them of resources available to manage it [ 196 ]. A meta-analysis of 25 RCTs reported that the “Coping with Depression” psychoeducational intervention, developed by Lewinsohn et al [ 197 ], was effective at treating depression, albeit with a small effect size ( d =0.28, 95% CI 0.18-0.38) [ 102 ].…”
Section: Resultsmentioning
confidence: 99%
“…Third, the theoretical basis of the intervention was confined to evidence-based components, consistent with the recommendations presented by Bakker et al [27] to create better and more rigorous mental health apps (MHapps). The chosen strategies were as follows: (1) focusing on nonclinical mental health, psychological well-being, and coping abilities, aiming to increase accessibility, enable preventive use, and reduce stigma, therefore avoiding the harmful effects of using mental illness labels [72]; (2) using self-monitoring and self-reflection—core features of many evidence-based psychological therapeutic techniques—to promote psychological growth and enable progress evaluations [73], with the advantage that MHapps make it possible for users to record self-monitoring data during their usual daily routines, while undergoing challenges or directly experiencing stressors [18]; (3) applying behavioral activation (ie, encourages individuals to engage in physiologically activating and psychologically rewarding activities) to boost self-efficacy, psychological well-being, and a repertoire of coping skills, since an app may promote self-discovery by encouraging an activity and then prompting reflection on the experience immediately after [74]; (4) presenting brief and passive psychoeducation to develop mental health literacy, in other words, to teach the participants about psychological processes underlying their distress and inform them about resources available to manage it [75]; (5) using real-time engagement to allow users to seek help for psychological challenges at the time they experience distress or soon after, thus opening new learning opportunities and applying coping strategies in ecologically valid contexts [76]; (6) promoting activities explicitly linked to specific mood problems to enhance understanding of cause-and-effect relationships between actions and emotions [77]; (7) using gamification—the use of “game-based mechanics, aesthetics and game thinking to engage people, motivate action, promote learning and solve problems” [78]—and intrinsic motivation to encourage app use via rewards and internal triggers, positive reinforcement, and behavioral conditioning, emergent approaches that may help counteract motivation problems and yield additional well-being outcomes; (8) providing reminders (email and push notifications) as external triggers for engagement, aiming to increase adherence and reduce dropout from self-help interventions [79]; and (9) conducting an experimental trial to establish the app’s efficacy before recommending it as an effective intervention.…”
Section: Discussionmentioning
confidence: 99%
“…MHapps have been developed with mood-tracking functionality, and a handful have been studied regarding their impact on ESA (Bakker & Rickard, 2017;Kauer et al, 2012;Morris et al, 2010;Rickard, Arjmand, Bakker, & Seabrook, 2016). MHL is the "knowledge and beliefs about mental disorders which aid their recognition, management or prevention" (Jorm et al, 1997), which can be gained through psychoeducation interventions (Macrodimitris, Hamilton, Backs-Dermott, & Mothersill, 2010). Internet delivered psychoeducation is effective at reducing depressive symptoms and distress (Brijnath, Protheroe, Mahtani, & Antoniades, 2016;Donker, Griffiths, Cuijpers, & Christensen, 2009), and can be embedded into MHapps.…”
Section: Apps Like Moodmission May Prevent Depressive and Anxietymentioning
confidence: 99%
“…Investigating these mediators is important to deduce what app features make a MHapp effective, and how MHapps can be improved by including or refining these features . MHL is the "knowledge and beliefs about mental disorders which aid their recognition, management or prevention" (Jorm et al, 1997), which can be gained through psychoeducation interventions (Macrodimitris, Hamilton, Backs-Dermott, & Mothersill, 2010). MHapps have been developed with mood-tracking functionality, and a handful have been studied regarding their impact on ESA (Bakker & Rickard, 2017;Kauer et al, 2012;Morris et al, 2010;Rickard, Arjmand, Bakker, & Seabrook, 2016).…”
Section: Introductionmentioning
confidence: 99%